On Total Vertex Irregularity Strength of Cocktail Party Graph - Kristiana Wijaya; S Slamin; Mirka Miller (Jurnal ILMU DASAR, 2011)
A vertex irregular total k-labeling of a graph G is a function λ from both the vertex and the edge sets to {1,2,3,,k} such that for every pair of distinct vertices u and x, λ(u)+∑λ(uv)≠λ(x)+∑λ(xy). uv∈E xy∈E. The integer k is called the total vertex irregularity strength, denoted by tvs (G ) , is the minimum value of the largest label over all such irregular assignments. In this paper, we prove that the total vertex irregularity strength of the Cocktail Party graph H2,n ,that is tvs(H2,n )= 3 for n ≥ 3.